Psychological status and its clinical determinants among people living with HIV/AIDS (PLWHA) in Northern Peninsular Malaysia - Mohd Radzniwan A Rashid; Alyani, M; Aida, J; Khairani, O; Jaafar, NRN; Tohid, H (Termedia Publishing House Ltd, 2024)
Indexed by WOS/SCOPUS